Development of high efficiency hazelnut shell breaking machine - HE Ting; LIU Ke; ZHANG Rui; REN Guangyue; LIU Zhaohan (Shipin yu jixie, 2024)
Objective: In order to solve the phenomenon of low mechanical shelling efficiency and high kernel breakage rate of hazelnut, a vertical cone shell breaking machine was designed with automatic adjustment of clearance through compression spring. Methods: The key structure of the shell breaker was composed of three core components: the vertical cone inner roller, the slatted screen outer roller and the pressure spring device, and the stress of the hazelnuts in the shelling cavity of the shell breaker was analyzed. Results: The main parameters of the vertical cone hazelnut shell breaker were determined: the taper of the uniform cone was 30°, the inclination angle of the inner roller bus was 75°, the half cone angle was 15°, the surface groove was spiral, the groove depth was 3 mm, the inclination angle of the outer roller bus was 73°, the half cone angle was 17°, the free stroke of the compression spring design was 230 mm, the middle warp was 160 mm, the wire diameter was 24 mm, the effective number of turns was 6, the total number of turns was 8, and the effective speed range of the inner roller was 229.2～881.5 r/min. Conclusion: This design can automatically adjust the compression amount of the vertical cone shell breaker and adjust the shell breaking gap through the feeding amount, which can adapt to the fruit shape size of different hazelnuts, so that the hazelnut shelling efficiency and kernel preparation rate can be improved.